THE EVALUATION OF SUPPLY CHAIN MANAGEMENT IN VEGETABLES DISTRIBUTION FROM THE TOURISM CITY OF BATU TO BALIKPAPAN AND BANJARMASIN CITY - Fidiantara, Odi (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study was to determine the implementation of Supply Chain Management’s key activities on the vegetables distribution  from The Tourism City of Batu to Balikpapan and Banjarmasin City. Key activities undertaken consisted of setting standards of customer service, select modes of transportation and set the load, inventory management, as well as manage information and fulfill orders. The purpose of this study was also to determine the factors that influence the continuity of vegetables distribution from  The Tourism City of Batu to Balikpapan and Banjarmasin City. This type of research is qualitative descriptive with case study approach. The results showed that the supply chain management’s key activities was first run when selecting vegetables to be harvested, then continues to the packing process, the vegetables from the fields was taken to the warehouse and packed in such a way to prevent damage and the quality is maintained up to the destination, then vegetables stacked in accordance strength of each to be loaded on a Fuso Truck and not change the quality, until finally ultimately sent to the destination. Key words: Supply Chain Management, Supply Chain Management’s Key Activities and Vegetables Distribution